Contrasting epidemiology and genetic variation of Plasmodium vivax infecting Duffy-negative individuals across Africa. (July 2021) - Lo, Eugenia; Russo, Gianluca; Pestana, Kareen; Kepple, Daniel; Abagero, Beka Raya; Dongho, Ghyslaine Bruna Djeunang; Gunalan, Karthigayan; Miller, Louis H.; Hamid, Muzamil Mahdi Abdel; Yewhalaw, Delenasaw; Paganotti, Giacomo Maria
Highlights: Vivax malaria is spreading across Africa, causing symptomatic and asymptomatic cases. P. vivax infections in Duffy-negative populations have low parasitemia. Sensitive and standardized methods are needed to detect vivax malaria in Africa. P. vivax in Duffy-negative Africans have evolved multiple times independently. The public health significance of vivax malaria in Africa should no longer be neglected. Abstract: Objectives: Plasmodium vivax malaria was thought to be rare in Africans who lack the Duffy blood group antigen expression. However, recent studies indicate that P. vivax can infect Duffy-negative individuals and has spread into areas of high Duffy negativity across Africa. Our study compared epidemiological and genetic features of P . vivax between African regions. Methods: A standardized approach was used to identify and quantify P. vivax from Botswana, Ethiopia, and Sudan, where Duffy-positive and Duffy-negative individuals coexist. The study involved sequencing the Duffy binding protein (DBP) gene and inferring genetic relationships among P. vivax populations across Africa. Results: Among 1215 febrile patients, the proportions of Duffy negativity ranged from 20–36% in East Africa to 84% in southern Africa. Average P. vivax prevalence among Duffy-negative populations ranged from 9.2% in Sudan to 86% in Botswana. Parasite density in Duffy-negative infections was significantly lower than in Duffy-positive infections. P. vivax in Duffy-negative populations were not monophyletic, with P. vivax in Duffy-negative and Duffy-positive populations sharing similar DBP haplotypes and occurring in multiple, well-supported clades. Conclusions: Duffy-negative Africans are not resistant to P. vivax, and the public health significance of this should not be neglected. Our study highlights the need for a standardized approach and more resources/training directed towards the diagnosis of vivax malaria in Africa.